1996
DOI: 10.1074/jbc.271.34.20227
|View full text |Cite
|
Sign up to set email alerts
|

SNAP-25 Is Required for a Late Postdocking Step in Ca2+-dependent Exocytosis

Abstract: Neurotransmitter and peptide hormone secretion require fusion between secretory vesicles and the plasma membrane, an exocytotic process activated by cytoplasmic Ca 2ϩ elevation. Understanding regulated secretion requires identification of molecular components that mediate docking and fusion reactions and delineation of rate-limiting steps that are Ca 2ϩ -regulated (1). The synaptic vesicle protein synaptobrevin and the presynaptic membrane proteins syntaxin and SNAP-25 1 are required components of the exocytot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
101
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(110 citation statements)
references
References 29 publications
8
101
1
Order By: Relevance
“…4). This observation agrees with an earlier study that showed that botulinum toxin E treatment cleaved the C-terminal 180 -206 sequence of SNAP-25 and destabilized the SNARE complexes in PC12 cells (32). It is also possible, however, that the inhibition was caused by other factors present in the COS-7 cell lysate, even though the cell lysate alone did not seem to affect the SNARE complex assembly/disassembly (data not shown).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…4). This observation agrees with an earlier study that showed that botulinum toxin E treatment cleaved the C-terminal 180 -206 sequence of SNAP-25 and destabilized the SNARE complexes in PC12 cells (32). It is also possible, however, that the inhibition was caused by other factors present in the COS-7 cell lysate, even though the cell lysate alone did not seem to affect the SNARE complex assembly/disassembly (data not shown).…”
Section: Discussionsupporting
confidence: 72%
“…Several elegant studies using synaptosome preparations and permeabilized PC12 cells have suggested that SNAP-25 may act in the late post-docking steps of exocytosis (20,(32)(33)(34). However, there are many questions that can only be answered by directly investigating neurons in vivo, especially at their functional synaptic junctions.…”
Section: Discussionmentioning
confidence: 99%
“…Whether syntaxin is involved in docking has been challenged by the finding that genetic knock-out of Drosophila syntaxin failed to impair vesicle docking . Furthermore, it has been documented that in PC12 cells large dense core vesicles still accumulate at the plasma membrane after BoNT/A treatment (Banerjee et al, 1996). In summary, the biochemical work, together with the morphological studies, indicates that vesicles can dock despite impaired or absent SNAREs, suggesting that synaptobrevin, syntaxin, and SNAP-25 are involved in events that occur between docking and fusion rather than being directly responsible for vesicle docking.…”
Section: Discussionmentioning
confidence: 90%
“…Higher order SDS-resistant ternary SNARE complexes have already been described in vitro (31). Interestingly, several groups have also implicated a role for the C terminus of SNAP-25 in a post-docking, fusion-catalyzing reaction (41)(42)(43). Some evidence exists to suggest the last 20 amino acids of this protein may play a role in Rab binding (44) and/or in activation of lipid-modifying reactions (45).…”
Section: Discussionmentioning
confidence: 99%